(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
In world literary studies, the study of the problem of classical poetics based on the principles of historicism, comparison, mutual influence, objectivity, and syncretism is becoming increasingly relevant at the present stage. In particular, the study of these scientific problems in the organic connection of Uzbek and Karakalpak literary studies can, in a certain sense, serve the development of both literatures. In this regard, it is becoming very important to research the issues of classical poetics from today’s perspective, to determine the common aspects of Uzbek and Karakalpak literary studies, to develop the features of the use of aruz, rhyme, and artistic devices in both poems, and to determine their place in Turkic literary studies.